Decarboxylative elimination: A new method for the synthesis of α,β-unsaturated ketones - Vichai Reutrakul (2018)
An efficient one-pot synthesis of α,β-unsaturated ketones via the decarboxylative elimination of sodium glycidates with lead tetraacetate is described. © 1979.